The genus Odontothrips in Iran with two new species (Thysanoptera: Thripidae) - Alavi, Jalil; Minaei, Kambiz (Zootaxa, 2022)
Host-plant associations among the 38 species of Odontothrips Amyot & Serville, and features of various structural characters in this genus, are discussed. An illustrated key to 9 species occurring in Iran is provided. Two new species are described from Iran based on specimens on flowers of various Fabaceae. O. bezii sp. n. is close to O. mongolicus Pelikan, and O. pitkini sp. n. is considered as the second species in the genus that has a tooth on the distal inner side of antennal segment II.